Innovative Approach to ESD Integration into School-Based Curriculum Development Modules for Elementary Schools - Hung, Li-Ching; Pan, Hsiang-Ju (Sustainability, 2025)
This study explores the curriculum development process and implementation challenges of a case school transitioning from a local to an ESD curriculum. Data were collected over 13 months through observations, interviews, and analysis of curriculum documents to examine the school’s curriculum development trajectory. The findings reveal that the school uses core concepts to link learning themes across grade levels, fostering a deeper and more coherent understanding of sustainability among students. Engagement and collaboration with key stakeholders provide diverse perspectives, and the school’s curriculum design is generally responsive to the concerns of its internal stakeholders. This study develops four perspective modules for ESD curriculum transformation: systemic, interdependent, comparative, and dialectical. In addition to analyzing the distinct applications of these perspectives, this research also discusses their usability in designing and implementing ESD in educational environments. These modules are designed to assist curriculum designers and practitioners in navigating the inherent complexities and contradictions of sustainability issues through innovative pedagogical approaches and to provide a valuable framework for educators transitioning from environmental education or local curricula to robust ESD implementation.